The clinical significance of T cell infiltration and immune checkpoint expression in central nervous system germ cell tumors - Zhou, Jiajun; An, Wenhao; Guan, Lei; Shi, Jinyu; Qin, Qiaozhen; Zhong, Shuai; Huang, Zheng; Liu, Rui; Wu, Chenxing; Ma, Zhong; Qi, Xueling; Jiang, Xiaoxia; et al. (Frontiers in Immunology, 2025)
BackgroundPrimary central nervous system germ cell tumors (CNS GCTs) are rare intracranial malignancies, and their tumor microenvironment plays a crucial role in tumor initiation and progression. However, the specific characteristics of the immune microenvironment and their clinical significance remain poorly understood.MethodsThis study included 93 paraffin-embedded tissue samples from 90 patients diagnosed with CNS GCTs. Immunohistochemistry and immunofluorescence staining were used to assess the infiltration patterns of T cell subsets (CD3+, CD4+, CD8+, Foxp3+) and the expression levels of immune checkpoints (CTLA-4, PD-1, PD-L1). Additionally, the study explored the relationship between these immune features and the patient’s clinical characteristics and prognosis.ResultsThe study revealed that germinomas exhibited significantly higher infiltration of CD4+ and Foxp3+ T cells compared to non-germinomatous GCTs (NGGCTs). Additionally, CTLA-4 expression was detected in 58.06% of cases, while PD-1 and PD-L1 were expressed in over 90%, with higher CTLA-4 levels in germinomas and elevated PD-L1 levels in NGGCTs. T cell infiltration was positively correlated with immune checkpoint expression, particularly in germinomas. The results also highlighted the strong immunosuppressive nature of the CNS GCTs’ tumor microenvironment. Furthermore, T cell infiltration and immune checkpoint expression were closely associated with clinical characteristics and prognosis. Notably, PD-1 expression was identified as an independent prognostic factor for progression-free survival (PFS) and recurrence-free survival (RFS).ConclusionOur study highlighted the distinct characteristics of T cell infiltration and the significant expression of immune checkpoints in CNS GCTs, revealing the highly heterogeneous and immunosuppressive nature of the tumor microenvironment. PD-1 expression was identified as an independent prognostic predictor, offering a foundation for enhancing risk stratification in CNS GCT patients. These findings also support the potential for future clinical applications of immune checkpoint inhibitors, such as PD-1 monoclonal antibodies.